Respuesta :

Answer:

x(t)=-t/4

y(t)=-t-2

(answer can vary)

Step-by-step explanation:

Many different ways to do... you are just introducing a different variable, t, to rewrite x and y.  We are rewriting x and y as functions of t.

So if we let -4x=t  then x=t/-4 or x=-t/4

So if -4x=t then t+y=-2 so y=-t-2

So you could write the following:

x(t)=-t/4

y(t)=-t-2

Answer: the answer is a)x=t,y=4t-2

Step-by-step explanation: I guessed and got it right so sorry i do not know how to explain anything but hopefully it helps someone in the future at least